Assessing the Effects of Word Exposure Frequency on Incidental Vocabulary Acquisition from Reading and Listening - Xiaoning, Chen; Feng, Teng (Chinese journal of applied linguistics, 2017)
This study investigated the effects of the frequency at which English as a foreign language (EFL) students were exposed to words from the input modes of reading and listening. Accordingly, 15 words of three frequency groups were selected. A total of 60 Chinese EFL students were recruited. The four test types of recall of form, recognition of form, recall of meaning, and recognition of meaning were administered to measure participants’ ability in building a form-meaning link. Immediate posttests were administered for assessing vocabulary development, and delayed posttests were administered two weeks later for assessing retention. The results revealed that new words could be learned incidentally in both modes, but more word knowledge was gained in reading. The effect of word exposure frequency on incidental vocabulary gains was significant for the four test types in both of the two modes. Since only partial word knowledge was acquired by both modes, it appeared that for the two modes to be a valuable source for incidental vocabulary learning, not only word exposure frequency, but also elaborate word processing is needed. Relevant implications for teaching and learning vocabulary are discussed.